Pengaruh Aplikasi Biogrouting Pada Tanah Vulkanis Terhadap Kuat Gesernya - Awaludin, Muhammad Fajar; Yuliani, Emma; Hendrawan, Andre Primantyo (Fakultas Teknik, Universitas Brawijaya, 2021)
Indonesia has many active volcanoes, one of which is Mount Kelud. The eruption of Mount Kelud produced a lot of volcanic ash. This study aims to determine the physical characteristics of the material and also the soil classification, and also to determine changes in the shear strength parameters due to the biogrouting process on the material with pseudomonas aeruginosa bacteria. From the results of this study, the material is bad with a GS value of 2.706. Samples with bacteria all experienced an increase in the internal shear angle of the samples with Dr 70%. The 70-10-Ps sample experienced the largest increase in internal shear angle, namely 942.4% when compared to 70-10-tb. Almost all samples with bacteria have decreased cohesion value. The sample with the smallest cohesion value was the 70-10-Ps sample when compared with the 70-10-Tb sample as a control.